2011
DOI: 10.1002/jor.21369
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors and their adaptors are regulated in macrophages after phagocytosis of lipopolysaccharide‐coated titanium particles

Abstract: Macrophages phagocytose metallic wear particles and produce mediators, which can induce cellular host response and aseptic implant loosening. Lipopolysaccharide (LPS) on the wear debris can stimulate macrophages via Toll-like receptor 4 (TLR4) and enhance the response. However, the precise functional role and interaction of TLRs and their adaptor molecules is still unclear. Rat bone marrow macrophages were stimulated with titanium particle (Ti) coated by LPS (Ti/LPS+) and LPS-free Ti (Ti/LPS-). mRNA levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 45 publications
5
64
0
Order By: Relevance
“…The mRNA expression levels were calculated to cells stimulated with Ti 1 LTA and Ti, compared to unstimulated control cells, respectively. 13 PCR specificities of all examined PRRs, PRRs-associated molecules, and GAPDH were confirmed by melting curve analysis.…”
Section: 29mentioning
confidence: 79%
See 1 more Smart Citation
“…The mRNA expression levels were calculated to cells stimulated with Ti 1 LTA and Ti, compared to unstimulated control cells, respectively. 13 PCR specificities of all examined PRRs, PRRs-associated molecules, and GAPDH were confirmed by melting curve analysis.…”
Section: 29mentioning
confidence: 79%
“…24,25 This suggests that assembly and activation of NLRP3 by wear particles could enhance periprosthetic osteolysis. 13 It has been also reported that the activated TLR2 cascade can potentiate joint inflammation via the NLRP3 cascade in crystal-induced arthritis. 26,27 This synergistic effect between TLR2 and NLRP3 may also enhance chronic inflammation around aseptically loose THA implants.…”
Section: Introductionmentioning
confidence: 98%
“…However, the resultant osteolysis induced by particle exposure was only partially reduced, suggesting that titanium particles may also induce osteolysis in a TLR2 and TLR4 independent pathway. In vitro stimulation of rat bone marrow derived macrophages by titanium particles coated with LPS increased TLR2 expression but decreased TLR4, 5, and 9, suggesting a self-protective regulation may exist to restrict an excessive response 39 .…”
Section: Challengesmentioning
confidence: 96%
“…TLR/PAMP interactions induce several immune cell functions, ranging from phagocytosis,11 migration,12 nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation13 to inflammatory cytokine expression 14. Accordingly, TLR9 activation leads to the expression of inflammatory cytokines, major histocompatibility complexes and homing molecules, via the detection of intracellular viral dsDNA in a MYD88-dependent manner 15.…”
Section: Introductionmentioning
confidence: 99%